Analisis Perbandingan Algoritma Perencanaan Jalur Robot Bergerak Pada Lingkungan Dinamis - Tonny Suhendra; Tri Kuntoro Priyambodo (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2017)
Development of technology and complexity of an environment (dynamic environtment), the use of algorithms in path planning becomes an important thing to do, problem to be solved by the path planning is safe patch (collision-free), second is the distance traveled, ie, the path length is generated from the robot start position to the current target position and the thirdtravel time, ie, the timerequired by the robot to reached its destination.this research uses ACO algorithm and A-star Algorithm to determine the influence of obstacles (simple environment) and also differences in the pattern of the target motion (linier and sinusoidal)on the ability of the algorithm in pathplanning for finding the shortest path. The test results show that for a simple environtment where the state of target and obstacles still static,the resukt that A-star algorithm is betterthan ACO algorithm both in terms of travel time and travel distance. Testing with no obstacles, seen from the distance travelled differences obtained of 0,57%, whereas for testing with obstacles difference of 9%. Testing in a complex environtment where the targets and obstacles which movesdinamically with a certain pattern, from the three environmental conditions that has been tested, ACO algorithm is better than A-star algorithm where the ACO algorithm can find a path with optimal distance or the sortest distance.